스트론튬 동위원소비를 이용한 자연 생육 및 인공 이식 감태 분류 - 서민지; 류종식; 최창근; MINJI SEO; JONG-SIK RYU; CHANG GEUN CHOI; NATHALIE VIGIER (Pada (Hanʼguk Haeyang Hakhoe), 2024)
The number of Ecklonia cava (E. cava) populations has been gradually declining due to natural and anthropogenic effects. Although many studies have been focused on ecological phenomena, there are little studies on chemical and isotopic characteristics of natural and transplanted E. cava. Here, we collected natural and transplanted E. cava in East Sea, and measured elemental and strontium isotope geochemistry (87Sr/86Sr ratios) in order to provide a powerful tool for classifying them. Elemental abundances of each E. cava follow the order of stipe (2.90% ± 3.17%) > blade (2.65 ± 2.98%) > holdfast (2.30 ± 2.04%), while those of 87Sr/86Sr ratios do the order of blade (0.709198 ± 0.000013) > stipe (0.709181 ± 0.000009) ≈ holdfast (0.709181 ± 0.000017). All E. cava have 87Sr/86Sr ratios higher than that of seawater, indicating they uptake Sr from rocks and cement with higher 87Sr/86Sr ratios. The results of t-test showed that there is little difference in elemental compositions between two populations (p value > 0.05, n = 30), while the difference in 87Sr/86Sr ratios is significant (p value < 0.05, n = 30). This study suggests that the 87Sr/86Sr ratios can be a useful tracer for classifying natural and transplanted E. cava. 감태(Ecklonia cava; E. cava)는 자연 및 인위적 영향으로 인해 개체 수가 점차 감소하고 있다. 현재까지 감태의 생태학적 특징에 관한 연구는 활발하게 수행되었으나, 자연 생육 및 인공 이식 감태의 화학 및 동위원소적 특성에 관한 연구는 이루어지지 않은 실정이다. 따라서 이번 연구에서는 동해안 해역에서 채취한 자연 생육 및 인공 이식 감태에 대한 무기화학조성(Na, K, Ca, Mg, and Sr) 및 스트론튬 동위원소 비(87Sr/86Sr) 분석을 통해 두 개체군의 부위별 지화학적 특성을 비교 분석하고, 분류 가능성을 조사하였다. 각 감태 개체군의 원소 함량은 줄기(2.90 ± 3.17%) > 잎(2.65 ± 2.98%) > 뿌리 (2.30 ± 2.04%) 순이며, 87Sr/86Sr 비는 잎(0.709198 ± 0.000013) > 줄기(0.709181 ± 0.000009) ≈ 뿌리(0.709181 ± 0.000017) 순서로 나타났다. 모든 부위에서 해수보다 높은 87Sr/86Sr 비를 나타내 87Sr/86Sr 비가 높은 암석과 시멘트에서 Sr가 흡수되었음을 지시한다. t-test 결과, 두 개체군 간의 원소 조성은 유의한 차이가 없는 것으로 나타났지만(p-value > 0.05, n = 30), 87Sr/86Sr 비는 유의미한 차이가 있는 것으로 나타났다(p-value < 0.05, n = 30). 이번 연구에서 제시한 것처럼 87Sr/86Sr 비는 자연 발생 감태와 인공 이식 감태를 분류하는 유용한 추적자가 됨을 시사한다.